Adverse Event Characteristics of Uhwangchungsim-won versus Cheonwangbosim-dan: A Pharmacovigilance Study Using Korea Adverse Event Reporting System (KAERS) Data - Yujin Choi; Hyeun-Kyoo Shin (Journal of Korean Medicine, 2026)
Objectives: This study aimed to analyze the characteristics of adverse event (AE) reports for two widely used traditional Korean herbal medicines, Uhwangchungsim-won and Cheonwangbosim-dan, using spontaneous reporting data from the Korea Adverse Event Reporting System (KAERS).Methods: Individual Case Safety Reports (ICSRs) for Uhwangchungsim-won and Cheonwangbosim-dan were extracted from the KAERS database (approval no. 2205A0042) covering 2012–2021. After data cleaning, 55 ICSRs for Uhwangchungsim-won and 37 for Cheonwangbosim-dan were included. Reporting characteristics, patient demographics, AE profiles by System Organ Class (SOC) and Preferred Term (PT), serious adverse events (SAEs), and causality were compared between the two drugs. Disproportionality analysis (Proportional Reporting Ratio, Reporting Odds Ratio, and Information Component) was performed using the 1,020 herbal medicine ICSRs as background data.Results: A total of 80 and 54 AEs were reported for Uhwangchungsim-won and Cheonwangbosim-dan, respectively. The primary reporter type differed significantly between the two drugs (p = 0.004): consumer/non-healthcare professional reports predominated for Uhwangchungsim-won (56.4%), while pharmacist reports predominated for Cheonwangbosim-dan (67.6%). Nervous system disorders were most frequent for Uhwangchungsim-won (33.8%), whereas Gastrointestinal disorders were most frequent for Cheonwangbosim-dan (38.9%). SAEs were rare (5.0% and 1.9%, respectively). Disproportionality analysis identified Somnolence and Dizziness as signals for Uhwangchungsim-won, and Vomiting for Cheonwangbosim-dan.Conclusions: The AE profiles of Uhwangchungsim-won and Cheonwangbosim-dan differ, with nervous system disorders predominating for the former and gastrointestinal disorders for the latter. The detected signals warrant further investigation and consideration for package insert updates.